EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DENGAN PENDEKATAN DEEP LEARNING DAN STEAM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF MATERI PECAHAN - Rahma Yuniar, Syahrani; Rosmiati; Ladyawati, Erlin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This This study aims to examine the effectiveness of STEAM-based Project-Based Learning (PjBL) integrated with a deep learning approach in improving the reflective thinking skills of fourth-grade elementary school students on fraction material. This research used a quantitative approach with a pretest-posttest design. Data were collected through tests. The results showed an improvement in students’ reflective thinking skills, as indicated by higher posttest scores. These findings indicate that STEAM-based PjBL with a deep learning approach is effective and can be used as an alternative learning model in elementary schools.